2022
DOI: 10.1186/s12929-022-00845-8
|View full text |Cite
|
Sign up to set email alerts
|

Functional and structural characteristics of HLA-B*13:01-mediated specific T cells reaction in dapsone-induced drug hypersensitivity

Abstract: Background Severe cutaneous adverse drug reactions (SCARs) are a group of serious clinical conditions caused by immune reaction to certain drugs. The allelic variance of human leukocyte antigens of HLA-B*13:01 has been strongly associated with hypersensitivities induced by dapsone (DDS). T-cell receptor mediated activation of cytotoxic T lymphocytes (CTLs) has also been suggested to play an essential role in pathogenesis of SCARs. However, HLA-B*13:01-DDS-TCR immune synapse that plays role in d… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
5
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 13 publications
(6 citation statements)
references
References 64 publications
1
5
0
Order By: Relevance
“…No intracellular antigen processing was involved in the HLA presentation of carbamazepine ( 77 ). Similar interaction was also seen in the hypersensitivity reaction induced by dapsone ( 78 ). The concept of the altered peptide repertoire model was demonstrated in the case of abacavir hypersensitivity syndrome in HLA-B*57:01-positive individuals ( 79 81 ).…”
Section: Pathogenesis In Drug Reaction With Eosinophilia and Systemic...supporting
confidence: 63%
“…No intracellular antigen processing was involved in the HLA presentation of carbamazepine ( 77 ). Similar interaction was also seen in the hypersensitivity reaction induced by dapsone ( 78 ). The concept of the altered peptide repertoire model was demonstrated in the case of abacavir hypersensitivity syndrome in HLA-B*57:01-positive individuals ( 79 81 ).…”
Section: Pathogenesis In Drug Reaction With Eosinophilia and Systemic...supporting
confidence: 63%
“…In the present study, we identified that LEV could hydrophobically bind to the A-E subpocket of the antigen-binding groove in HLA-B∗13:01, while dapsone and salazosulfapyridine have been reported to bind toward the F pocket of the same groove. 25 , 26 , 27 , 28 The differences in binding site may be attributed to their different chemical scaffolds. LEV has a bigger structure compared to dapsone and salazosulfapyridine, which was not suitable in the narrow F pocket and, therefore, favorably located in the larger cleft consisting of A-E pocket.…”
Section: Discussionmentioning
confidence: 99%
“…demonstrated that three different amino acids in the antigen-binding site (I94, I95, and R97 in HLA-B∗13:01, and T94, W95, and T97 in HLA-B∗13:02) played important roles in dapsone selectivity through creating steric hindrance, changing van der Waals interactions and affecting the electrostatic properties of the dapsone-binding pocket. 26 …”
Section: Discussionmentioning
confidence: 99%
“… Zhao et al (2021) investigated that dapsone and its metabolite nitroso-dapsone are selectively interacted with HLA-B*13:01 to activate CTLs related cytotoxicity. Recently, Jiang et al (2022) demonstrated that HLA-B*13:01-dapsone-TCR immune molecular mechanism is formed according to pharmacological-interaction model.…”
Section: Hla Susceptibility To Drug-induced Scarmentioning
confidence: 99%